DETERMINANTS OF WORK READINESS AMONG INDONESIAN UNIVERSITY STUDENTS: A SYSTEMATIC LITERATURE REVIEW IN THE ERA OF MERDEKA BELAJAR KAMPUS MERDEKA - Desti Agustin; Nono Hery Yoenanto; Fitri Andriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT High unemployment rates among Indonesian university graduates and persistent skill mismatches highlight the critical need to understand work readiness determinants. This PRISMA-guided systematic literature review synthesized 16 primary studies (2021–2025) retrieved from DOAJ and GARUDA databases to identify dominant factors influencing work readiness of Indonesian university students in the Merdeka Belajar Kampus Merdeka (MBKM) era. Quality appraisal was performed using the AXIS Tool. Three interconnected categories emerged: (1) individual factors (self-efficacy, soft skills, hard skills, career adaptability, communication, digital literacy), present in 87.5% of studies and consistently the strongest predictor; (2) practical experience factors (internships, PKL, MSIB/MBKM programs), identified in 50% of studies and serving as a vital bridge between academic knowledge and workplace demands; and (3) institutional/environmental factors (entrepreneurship education and MBKM policy implementation), found in 37.5% of studies. Cultural elements such as collectivism, familial influence, and regional variations significantly moderated the weight of each factor. The findings indicate that enhancing work readiness requires a culturally sensitive, holistic approach combining psychological capital development, mandatory real-world experience, and region-specific institutional support. These insights offer actionable guidance for universities, policymakers, and students to reduce graduate unemployment and align higher education outcomes with rapidly evolving labour-market needs.